1968
DOI: 10.1111/j.1476-5381.1968.tb07055.x
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic action of morphine‐N‐oxide

Abstract: The analgesic activity of morphine‐N‐oxide in mice and rats has been investigated and compared with that of morphine. Both morphine and morphine‐N‐oxide were more active when given subcutaneously than when given intraperitoneally. Given subcutaneously, morphine was 11–22 times more potent than morphine‐N‐oxide and when given intraperitoneally it was 39–89 times more potent. The potencies depended on the test situation and the species of animal used. In animals pretreated with amiphenazole or tacrine, the analg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1971
1971
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…For example, the pyrrole ring of nicotine is metabolized by flavin-containing monooxygenase 3 (FMO3) in the human liver to ( S )-nicotine 1′-N-oxide, albeit a relatively minor pathway of nicotine metabolism [ 7 , 8 , 9 ]. Similarly, morphine is metabolized to its N-oxide in the liver [ 10 ]. Trimethylamine is a metabolite derived from choline as well as carnitine.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the pyrrole ring of nicotine is metabolized by flavin-containing monooxygenase 3 (FMO3) in the human liver to ( S )-nicotine 1′-N-oxide, albeit a relatively minor pathway of nicotine metabolism [ 7 , 8 , 9 ]. Similarly, morphine is metabolized to its N-oxide in the liver [ 10 ]. Trimethylamine is a metabolite derived from choline as well as carnitine.…”
Section: Introductionmentioning
confidence: 99%
“…However, this protocol has only been tested with (and is optimized for) the use of subcutaneously injected morphine as the analgesic agent. We have chosen subcutaneous injection as it has been previously demonstrated that morphine produces more robust analgesic effects when administered subcutaneously versus intraperitoneally ( Bianchi and Franceschini, 1954 ; Fennessy, 1968 ). However, intraperitoneal injection is also acceptable with an appropriately adjusted dose.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
“…Morphine-N-oxide is also an analgesic [12], while other N-oxides mimic the physiccological activities of the corresponding alkaloids (I. Brondz and J. Røe, to be published) [13].…”
Section: Resultsmentioning
confidence: 99%